2023
DOI: 10.21203/rs.3.rs-3227228/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeographic evolution of horseshoe bat sarbecoviruses in Vietnam and implications for the origins of SARS-CoV and SARS-CoV-2

Alexandre HASSANIN,
Vuong Tu,
Tamás Görföl
et al.

Abstract: Previous studies on horseshoe bats (Rhinolophus spp.) have described many coronaviruses related to SARS-CoV (SARSCoVr) in China and only a few coronaviruses related to SARS-CoV-2 (SARSCoV2r) in Yunnan, Cambodia, Laos and Thailand. Here, we report the results of several field missions carried out in 2017, 2021 and 2022 across Vietnam during which 1,218 horseshoe bats were sampled. We assemble 38 Sarbecovirus genomes: 26 SARSCoVr from R. thomasi; six SARSCoVr and four SARSCoV2r from R. affinis; and two recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The origin of SARS-CoV-2 is an issue in the field of virology. Importantly, the discovery of SARS-CoV-2-related coronaviruses (SC2r-CoVs) in feces or rectal swabs of horseshoe bats (genus Rhinolophus ) (e.g., RaTG13, 6 RmYN02, 7 RacCS203, 8 RpYN06, 9 RshSTT182, 10 Rc-o319, 11 Rp22DB159 12 ) provided evidence supporting that SARS-CoV-2 originated from the zoonotic transmission of certain SC2r-CoV into the human population. A clear difference between SARS-CoV-2 and SC2r-CoVs is the presence of the furin cleavage site (FCS) only in the spike (S) protein of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of SARS-CoV-2 is an issue in the field of virology. Importantly, the discovery of SARS-CoV-2-related coronaviruses (SC2r-CoVs) in feces or rectal swabs of horseshoe bats (genus Rhinolophus ) (e.g., RaTG13, 6 RmYN02, 7 RacCS203, 8 RpYN06, 9 RshSTT182, 10 Rc-o319, 11 Rp22DB159 12 ) provided evidence supporting that SARS-CoV-2 originated from the zoonotic transmission of certain SC2r-CoV into the human population. A clear difference between SARS-CoV-2 and SC2r-CoVs is the presence of the furin cleavage site (FCS) only in the spike (S) protein of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of bat coronaviruses (sarbecoviruses) in Southeast Asia very similar to SARS-CoV-2 (1,2) is key to deciphering SARS-CoV-2's origin. They are remarkable the Rhinolophus malayanus BANAL52 isolate from Laos (1) and the Rhinolophus pusillus Rp22DB159 isolate from Vietnam (2) which are the closest known relatives of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…In general, direct contact between humans and bats is limited, and an intermediate species often plays a role in the transmission of emerging viruses from bats to humans (3), however, several studies have recently concluded that SARS-CoV-2 emerged directly from a bat virus (1,2). Bat Rhinolophus species circulating in Southeast Asian harbour a diversity of coronaviruses (e.g., BANAL52, Rp22DB159) capable of infecting very distant mammal species, including humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infection of human cells by SARS-CoV-2 is greatly favoured by a positive region in the furin cleavage site at the S1/S2 junction of the viral spike glycoprotein (1)(2)(3)(4)(5). It has no analogy in other Becoronavirus sarbecoviruses, including the new discovered Laos and Vietnam bat coronaviruses closest known relatives to SARS-CoV-2 (6,7). The key evolutionary step leading to the pandemic virus was the acquisition in a progenitor of SARS-CoV-2 the S gene 12 nucleotide insert encoding the polybasic furin site (PRRA).…”
Section: Introductionmentioning
confidence: 99%